2017
DOI: 10.1038/s41598-017-00318-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in CRYGC are associated with congenital cataracts in Chinese families

Abstract: Congenital cataract (CC), responsible for about one-third of blindness in infants, is a major cause of vision loss in children worldwide. 10–25% of CC cases are attributed to genetic causes and CC is a clinically and genetically highly heterogeneous lens disorder in children. Autosomal dominant (AD) inheritance is the most commonly pattern. 195 unrelated non-syndromic ADCC families in this study are recruited from 15 provinces of China. Sanger sequencing approach followed by intra-familial co-segregation, in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…The entry for the present mutation (c.432C>G) has been also reported in ClinVar; however, there was no information regarding the phenotype. In a study by Zhong et al [2017], 8 different mutations in CRYGC including c.432C>G in a Chinese population with congenital nuclear cataract in which congenital cataract was also associated with microphthalmos similar to Case 2 were reported. Gonzalez-Huerta et al…”
Section: Discussion/conclusionmentioning
confidence: 95%
“…The entry for the present mutation (c.432C>G) has been also reported in ClinVar; however, there was no information regarding the phenotype. In a study by Zhong et al [2017], 8 different mutations in CRYGC including c.432C>G in a Chinese population with congenital nuclear cataract in which congenital cataract was also associated with microphthalmos similar to Case 2 were reported. Gonzalez-Huerta et al…”
Section: Discussion/conclusionmentioning
confidence: 95%
“…Congenital cataract (CC) refers to a lens opacity present at birth, responsible for 10–30% of all vision loss in infants worldwide ( 3 ). In industrialized countries, the occurrence of CC is 1–6 cases per 10,000 births, whereas in China it is ~5 per 10,000 births ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a total of 32 variants in CRYGC gene have been reported to be associated with congenital cataract ( Heon et al, 1999 ; Ren et al, 2000 ; Santhiya et al, 2002 ; Gonzalez-Huerta et al, 2007 ; Devi et al, 2008 ; Yao et al, 2008 ; Zhang et al, 2009 ; Kumar et al, 2011 ; Guo et al, 2012 ; Li et al, 2012 ; Kondo et al, 2013 ; Reis et al, 2013 ; Gillespie et al, 2014 ; Prokudin et al, 2014 ; Li et al, 2016 ; Ma et al, 2016 ; Patel et al, 2017 ; Sun et al, 2017 ; Zhong et al, 2017 ; Astiazaran et al, 2018 ; Li et al, 2018 ; Zhang et al, 2019 ; Zhuang et al, 2019 ; Berry et al, 2020 ; Taylan Sekeroglu et al, 2020 ; Fernandez-Alcalde et al, 2021 ; Karahan et al, 2021 ; Rechsteiner et al, 2021 ), but there were few reports about the de novo mutations. In 2017, Zhong et al reported a frameshift mutation (p.Asp65ThrfsX38) which might be de novo ( Zhong et al, 2017 ). In 2021, Rechsteiner et al reported a de novo mutation p.Glu107GlyfsX56, which causes cataracts and microphthalmia ( Rechsteiner et al, 2021 ), and Fernández-Alcalde et al reported a de novo mutation p.Leu145GlyfsX5 ( Fernandez-Alcalde et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital cataract is one of the most common causes of blindness in children, with an estimated prevalence of 1–6 cases per 10,000 live births ( Santana and Waiswo, 2011 ). About 8.3%–25% of congenital cataract cases present Mendelian inheritance; autosomal dominant inheritance pattern is the most common, but autosomal recessive and X-linked patterns have also been reported ( Merin and Crawford, 1971 ; Francois, 1982 ; Zhong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%